Faktor-Faktor Gejala Alam Tanah Longsor dan Motif Yang Mempengaruhi Pola Pemukiman Penduduk di Desa Samar Kecamatan Pagerwojo Kabupaten Tulungagung - Afifudin Bagus Wildani; Firsta Putri Enjela Zainal Arifin; Nerlis Cholifah; Zulfa Rofi’atunnisa; Hany Nurpratiwi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Landslide disaster is one of the geological natural disasters. Landslide disasters that occur in Indonesia from year to year are becoming more frequent. The landslide disaster recently occurred on Jalan Raya Samar, Samar Village, Pagerwojo District, Tulungagung Regency, East Java Province on Saturday 8 October 2022. Samar Village is located in a highland area with a fairly dense distribution of settlements. From this, the factors that influence the occurrence of landslides and what are the motives that influence the pattern of settlement of the population so that people survive in the village of Samar, need to be studied further. Through this research, it is expected to be able to obtain ideas regarding the factors of natural phenomena and motives that influence the pattern of settlement of residents in the Samar Village area. This research was conducted using qualitative methods by conducting observations, field surveys, interviews, and literature studies because the researchers wanted to obtain data related to the natural phenomena of landslides and the motives that influence the pattern of population settlements. The research results obtained are several reasons for local people to survive in landslide-prone areas.